8y+3(y-8)=6(y+1)-4

Simple and best practice solution for 8y+3(y-8)=6(y+1)-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8y+3(y-8)=6(y+1)-4 equation:


Simplifying
8y + 3(y + -8) = 6(y + 1) + -4

Reorder the terms:
8y + 3(-8 + y) = 6(y + 1) + -4
8y + (-8 * 3 + y * 3) = 6(y + 1) + -4
8y + (-24 + 3y) = 6(y + 1) + -4

Reorder the terms:
-24 + 8y + 3y = 6(y + 1) + -4

Combine like terms: 8y + 3y = 11y
-24 + 11y = 6(y + 1) + -4

Reorder the terms:
-24 + 11y = 6(1 + y) + -4
-24 + 11y = (1 * 6 + y * 6) + -4
-24 + 11y = (6 + 6y) + -4

Reorder the terms:
-24 + 11y = 6 + -4 + 6y

Combine like terms: 6 + -4 = 2
-24 + 11y = 2 + 6y

Solving
-24 + 11y = 2 + 6y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-6y' to each side of the equation.
-24 + 11y + -6y = 2 + 6y + -6y

Combine like terms: 11y + -6y = 5y
-24 + 5y = 2 + 6y + -6y

Combine like terms: 6y + -6y = 0
-24 + 5y = 2 + 0
-24 + 5y = 2

Add '24' to each side of the equation.
-24 + 24 + 5y = 2 + 24

Combine like terms: -24 + 24 = 0
0 + 5y = 2 + 24
5y = 2 + 24

Combine like terms: 2 + 24 = 26
5y = 26

Divide each side by '5'.
y = 5.2

Simplifying
y = 5.2

See similar equations:

| 2x-4=1x+3 | | 12=0.92 | | 2cos(3x)cos(x)=0 | | 7c=150 | | X-380+x^2=0 | | .08x-.1=16.7 | | 3x-5=3(x+8) | | (-52)(35)= | | -13.3p+10.52=18.28-12.9p | | r^2+4r=45 | | 2c-d=1 | | 16=-9-a | | Y=126 | | 9x+3=3(17-x) | | 5/6p=14 | | 7*p^2+56*p+112=0 | | -3a-4=33 | | 3sec(x)+4=0 | | 9x+3=3(17-y) | | 3/7r=6 | | -2.3u-11.27=2.3u-13.49-15.7u | | 9x=3x-30 | | (-3)(-4)(-2)(-10)(-7)= | | 2h-9=h+20 | | 10y+3y-2=4y-y+8 | | 1=-1+w | | 7x+6=9x+11-7x | | 3squared-2(11-8)squared=36x | | 4/3x=1/10 | | 10y-3y= | | 2x^3+6x^2+3x+9=0 | | -24=36+49x |

Equations solver categories